Use an Entrepreneurial Mindset to Find Success and Fulfillment at Work. - Shrimpton, Erin (linkedin.com, 2021)
Learn how to harness entrepreneurial thinking and behavior to build your motivation, adaptability, and future focus—all in pursuit of success and fulfilment at work and in life.